1975
DOI: 10.1159/000225061
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Differentiated (Non-Medullary) Thyroid Cancer

Abstract: Differentiated thyroid cancers were found in mother and son. The diagnosis was made first in the boy where papillary and follicular cancer with lymph node involvement and lung metastatic dissemination was diagnosed at the age of 9. Treatment by surgery, radioiodine and thyroid hormones was highly effective. 1 year later, thyroid surgery was performed on his mother but the diagnosis of poorly differentiated follicular thyroid cancer was made only 4 years later when the primary tumour was already unresectable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 2 publications
1
16
2
Order By: Relevance
“…A common genetic predisposition could account for the occurence of papillary thyroid carcinoma together with parathyroid adenoma/hyperplasia and adenoma of the pituitary gland, justifying the creation of the MEN III group. A familial non-medullary thyroid carcinoma has recently been described by Nemec et al (1975), but in our case no familial factors could be discovered.…”
Section: Discussioncontrasting
confidence: 54%
“…A common genetic predisposition could account for the occurence of papillary thyroid carcinoma together with parathyroid adenoma/hyperplasia and adenoma of the pituitary gland, justifying the creation of the MEN III group. A familial non-medullary thyroid carcinoma has recently been described by Nemec et al (1975), but in our case no familial factors could be discovered.…”
Section: Discussioncontrasting
confidence: 54%
“…However, case reports of DTC in monozygotic twins and in a mother and son were published in 1955 and 1975, respectively, [21, 22]. More recently, population studies showed that the risk of DTC was elevated in individuals with a first-degree relative having DTC [23, 24].…”
Section: Prognostic Factors Of Ptcmentioning
confidence: 99%
“…Another description in 1975 of a PTC in a 9-year-old boy, widely metastatic to lymph nodes and lung was described; a poorly differentiated carcinoma found in his mother without environmental exposure. 2 The incidence of thyroid carcinoma is increasing, and the rise in the incidence of this cancer is the fastest among common human cancers, becoming the seventh most common tumor in women, with a current incidence of 33,550 new cases per year and a prevalence of 366,466 cases. 3 Thyroid carcinoma derived from follicular cells [papillary and follicular thyroid carcinoma (FTC), poorly differentiated thyroid carcinoma, and anaplastic thyroid carcinoma] is the most common endocrine malignancy.…”
mentioning
confidence: 99%